Combination of dapagliflozin and pioglitazone lacks superiority against monotherapy in streptozotocin-induced nephropathy - Aneta Cinakova; Diana Vavrincova-Yaghi; Peter Krenek; Jan Klimas; Eva Kralova (Scientific Reports)
Abstract Oxidative stress and apoptosis are highly engaged in development of diabetic nephropathy (DN). In monotherapy, dapagliflozin and pioglitazone positively modulate target organ damage even independently of their hypoglycaemic effect. This study evaluated whether a simultaneous PPARγ activation and SGLT cotransporter inhibition offer superior protection against DN-related oxidative and apoptotic processes in a T1DM rat model. Diabetes was induced in Wistar rats using streptozotocin (55 mg/kg, i.p.). The rats received daily chow containing dapagliflozin (10 mg/kg), pioglitazone (12 mg/kg) or their combination. Six weeks after STZ administration, histological and molecular analyses were performed in excised kidneys. STZ-induced DN was demonstrated by the propagation of apoptotic (Bax, p53, Casp3) and oxidative reactions (Gp91phox, MnSOD) and disrupted nitric oxide signalling (eNOS, Hsp90, Cav1). Kidney damage molecule expression (Kim1, Nphs1) revealed a deceleration of kidney damage by pioglitazone and dapagliflozine monotherapies. The monotherapy also reduced apoptosis, oxidative stress, and partially restored NO signalling. The combined therapy ameliorated glomerulosclerosis but in other measured parameters, it reached the effect of the monotherapies except for Hsp90 expression modulation. Both dapagliflozin and pioglitazone exert protective character in kidneys when used in monotherapy. The combined therapy does not exhibit an expected additive effect within modulating oxidative stress, NO signalling or apoptosis.